(untitled) (Research, Society and Development, 2021)
Objective: to investigate the knowledge of intensive care nurses about prevention and risk assessment related to PPL and the importance of using nursing care protocols. Methods: This is an exploratory-descriptive study with a qualitative approach. The participants in this study are composed of intensive care nurses, ICU coordinating nurse and nursing manager, in addition to nurses responsible for the Dressing and Patient Safety Commission, totaling ten participants. Data were collected between March and December 2019. Individual semi-structured interviews were applied and later, the respondents’ responses were transcribed in full and analyzed through the Collective Subject Discourse. Results: The analysis of the statements was based on six questions, which resulted in nine CSDs. The responses were subdivided into “Category A” and “Category B” when two different types of responses were obtained. As a result, questions 1, 2 and 3 show CSD in categories A and B, while questions 4, 5 and 6 only have CSD in “Category A”. Conclusion: The study enabled a better understanding of the conditions experienced by nurses working in the ICU, pointing out potentials, difficulties and limitations in the prevention and treatment of PPL.